Comparative description of the Mediterranean erigonine spider Diplocephalus guidoi n. sp. (Araneae, Linyphiidae) - Frick, Holger; Isaia, Marco (Zootaxa, 2012)
MCSNB: Museo Civico di Scienze Naturali “E. Caffi”, Bergamo, Italy; NMBE: Natural History Museum of Bern, Switzerland; HF: Private Collection Holger Frick; MI: Private Collection Marco Isaia, stored at Life Science and System Biology, University of Turin. ALE: anterior lateral eyes; AME: anterior median eyes; ARP: anterior radical process; DP: dorsal plate; DSA: distal suprategular apophysis; E: embolus; EM: embolic membrane; ISA: inner suprategular apophysis; PC: paracymbium; PLE: posterior lateral eyes; PME: posterior median eyes; RTP: radical tailpiece; ST: subtegulum; T: tegulum; TmI: Trichobothrium on metatarsus I; VP: ventral plate.